Inverted-U relationship between innovation and survival: Evidence from firm-level UK data - Francesco Guidi; Edna Solomon; Eshref Trushin; Mehmet Ugur (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Theoretical and empirical work on innovation and firm survival has produced varied and often conflicting findings. In this paper, we draw on Schumpeterian models of competition and innovation and stochastic models of firm dynamics to demonstrate that the conflicting findings may be due to linear specifications of the innovation-survival relationship. We demonstrate that a quadratic specification is appropriate theoretically and fits the data well. Our findings from an unbalanced panel of 39,705 UK firms from 1997-2012 indicate that an inverted-U relationship holds for different types of R&D expenditures and sources of funding. We also report that R&D intensity is more likely to increase survival when firms are in more concentrated industries and in Pavitt technology classes consisting of specialized suppliers of technology and scale-intensive industries. Finally, we report that the effects of firm and industry characteristics as well as macroeconomic environment indicators are all consistent with prior findings. The results are robust to step-wise modeling, controlling for left truncation and use of lagged values to address potential simultaneity bias.
Additional information: This paper proposes and tests a quadratic specification for the relationship between R&D intensity and firm survival, using a rich dataset on UK firms. It argues that the linear specification in the exiting literature may be subject to misspecification bias.
Keywords: C41; D21; D22; L1; O3; 330; innovation; R&D; firm dynamics; survival anaysis